Positive electrode material and preparation method and application thereof

By using the combination of LiaNixCoyMzNpO2 compound and modification additive in the lithium battery positive electrode material, a positive electrode material with a specific structure is solved, and the problem of difficult to take into account the capacity and safety of the ternary positive electrode material in lithium batteries is achieved, and high discharge capacity is achieved. Excellent electrochemical performance and high safety performance effects.

CN119275246APending Publication Date: 2025-01-07CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310805945.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-03
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing ternary positive electrode materials have increased their activity after capacity increases in lithium batteries, resulting in safety problems, especially the reduction of thermal runaway triggering temperature, making it difficult to take into account high capacity and high safety performance.

Method used

Using a positive electrode material with chemical composition of LiaNixCoyMzNpO2, combined with a modification additive, aligned along the radial direction of the secondary microspheres through primary particles, and a cladding layer is formed on the surface, using a sheet-like precursor and a group VA element modifier. The synergistic effect of the sintering temperature and time is adjusted to form long strip primary particles and spherical secondary microsphere structures.

Benefits of technology

The discharge specific capacity of lithium batteries, first week Coulomb efficiency and thermal runaway trigger temperature are improved, the safety and electrochemical performance of the material are enhanced, and it is suitable for high energy density and high safety lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119275246A_ABST
    Figure CN119275246A_ABST
Patent Text Reader

Abstract

The invention discloses a positive electrode material and a preparation method and application thereof. The positive electrode material comprises a compound with the chemical composition of LiaNixCoyMzNpO2 and a modification additive, in the compound with the chemical composition of LiaNixCoyMzNpO2, a is greater than or equal to 0.9 and less than or equal to 1.2, x is greater than or equal to 0 and less than or equal to 1, y is greater than or equal to 0 and less than or equal to 1, z is greater than or equal to 0 and less than or equal to 1, and 1lt is 0; a is smaller than or equal to 0.1, p is smaller than or equal to 0.1, the values of x, y and z are not 0 at the same time, the values of a, x, y, z and p meet the electrically neutral principle, M is selected from at least one of VIIB group elements or IIIA group elements, N is selected from at least one of VA group elements, and the performance additive is selected from oxides containing the IIIA group elements; the positive electrode material is a secondary microsphere formed by gathering primary particles, and the primary particles are strip-shaped. By adopting the positive electrode material, the discharge capacity, the first cycle efficiency and the thermal runaway triggering temperature of the positive electrode material are improved, and the positive electrode material can be applied to a high-performance lithium battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium batteries, and in particular to a positive electrode material and a preparation method thereof and application in lithium batteries. Background Art

[0002] With the increasing popularity of electric vehicles and mobile terminals, the shipment of lithium-ion batteries continues to grow. Lithium-ion batteries are mainly composed of key materials such as positive electrodes, negative electrodes, separators and electrolytes. Among them, the positive electrode material determines the key indicators of lithium-ion batteries such as energy density, cycle life, safety, and cost, and is the material that the research field focuses on.

[0003] Currently commercial cathode materials mainly include olivine-structured LiFePO 4 , spinel structure LiMn 2 O 4 , layered structure of LiCoO 2 And layered ternary cathode materials, etc. Among them, the layered ternary cathode materials have a high theoretical specific capacity and are the preferred cathode materials for high-performance power batteries. However, in actual applications, the capacity that the ternary cathode materials can exert is far lower than the theoretical capacity. Improving the actual discharge capacity of the ternary cathode materials is of great significance to improving the range of power batteries.

[0004] CN114656000A discloses a nickel-cobalt-manganese-oxide lithium material, which reduces the Li / Ni mixing by doping the transition metal layer and the lithium layer with different valence states of antimony (different ionic radii), thereby improving the stability of the bulk and surface from the material level. However, after the capacity of the ternary positive electrode material is improved, the activity of the material becomes higher, but the thermal runaway trigger temperature is reduced after being assembled into a full battery, and the safety problem is significant. Therefore, the problem that the ternary positive electrode material needs to have both high capacity and high safety performance is very prominent. Summary of the invention

[0005] The present invention aims to solve the problem that the capacity and safety of ternary positive electrode materials in the prior art are difficult to balance, and provides a positive electrode material and a preparation method and application thereof. The positive electrode material of the present invention has excellent electrochemical performance and safety performance when used in lithium batteries, which are specifically manifested in high discharge specific capacity, high first cycle efficiency, and high thermal runaway temperature of the whole battery.

[0006] The first aspect of the present invention provides a positive electrode material, the positive electrode material comprising a chemical composition of Li a Ni x Co y M z N p O 2 Compound and modification aid, the chemical composition is Li a Ni xCo y M z N p O 2 In the compound of, 0.9 ≤ a ≤ 1.2, 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, 0 ≤ z ≤ 1, 0 < p ≤ 0.1, x, y, and z are not all 0 at the same time, and the values of a, x, y, z, and p satisfy the principle of electroneutrality. The M is selected from at least one of the elements in Group VIIB or Group IIIA, the N is selected from at least one of the elements in Group VA, and the modification assistant is selected from the oxides containing the elements in Group IIIA; the positive electrode material is a secondary microsphere formed by the aggregation of primary particles, and the primary particles are strip-shaped.

[0007] In the above technical solution, the chemical composition is Li a Ni x Co y M z N p O 2 In the compound of, 0.5 ≤ x ≤ 0.95, 0 ≤ y ≤ 0.5, 0 ≤ z ≤ 0.5, 0 < p ≤ 0.05, x, y, and z are not all 0 at the same time, preferably x, y, and z are not 0 at the same time, and the values of a, x, y, z, and p satisfy the principle of electroneutrality.

[0008] In the above technical solution, the element in Group VIIB is preferably Mn, the element in Group IIIA is preferably Al, and the element in Group VA is selected from at least one of N, P, Sb, and Bi.

[0009] In the above technical solution, the M is preferably at least one of Mn and Al, and the N is preferably at least one of P, Sb, and Bi.

[0010] In the above technical solution, for the positive electrode material, in terms of mole fraction:

[0011] Li a Ni x Co y M z N p O 2 100 parts of the compound of;

[0012] The modification assistant is more than 0 parts and less than 5 parts.

[0013] In the above technical solution, the oxide of the element in Group IIIA of the modification assistant forms a coating layer on the surface of the compound with the chemical composition of Li a Ni x Co y M z N p O 2 of.

[0014] In the above technical solution, the primary particles are arranged along the radial direction of the secondary microspheres, and the median particle size of the secondary microspheres is 1.0-20.0 μm, wherein the median particle size refers to the particle size corresponding to when the cumulative particle size distribution percentage of the secondary microspheres reaches 50%.

[0015] In the above technical solution, the aspect ratio of the primary particles is 1.05-60.0, preferably 1.5-30.0, and more preferably 1.5-20.0.

[0016] The second aspect of the present invention provides a method for preparing the above-mentioned positive electrode material, comprising:

[0017] (1) mixing a cathode material precursor, a lithium source, and a modifier containing a Group VA element, and sintering them once to obtain an intermediate product;

[0018] (2) The intermediate product is mixed with oxides of Group IIIA elements and subjected to secondary sintering to obtain the positive electrode material.

[0019] In the above technical solution, the chemical composition of the positive electrode material precursor is Ni x Co y M z (OH) 2 , 0≤x≤1, 0≤y≤1, 0≤z≤1, preferably 0.5≤x≤0.95, 0≤y≤0.5, 0≤z≤0.5, the values ​​of x, y and z are not 0 at the same time, and the values ​​of x, y and z satisfy the principle of electrical neutrality.

[0020] In the above technical solution, the morphology of the positive electrode material precursor is microspheres formed by flake accumulation. The average thickness of the flakes is 1-500nm, preferably 1-200nm.

[0021] In the above technical solution, the lithium source is preferably selected from lithium nitrate (LiNO 3 )、LiCl、LiCO 2 CO 3 ), lithium hydroxide (LiOH), lithium hydroxide monohydrate (LiOH·H 2 O), lithium oxide (Li 2 O), lithium acetate (CH 3 COOLi and lithium oxalate (Li 2 C 2 O 4 ) at least one of.

[0022] In the above technical solution, the molar ratio of the positive electrode material precursor to the lithium source (in terms of Li element) is 1:(0.9-1.2).

[0023] In the above technical solution, the modifier containing the Group VA element is preferably selected from at least one of nitrates, chlorides, carbonates, hydroxides, oxides, acetates and oxalates containing the Group VA element.

[0024] In the above technical scheme, the molar ratio of the positive electrode material precursor and the modifier containing the VA group element (calculated as the VA group element) is 1:s, and the value range of s is greater than 0 to 0.1. Preferably, the molar ratio of the positive electrode material precursor and the modifier containing the VA group element (calculated as the VA group element) is 1:(0.001-0.05).

[0025] In the above technical solution, the primary sintering is programmed temperature sintering, the heating rate is preferably 0.5-10°C / min, the primary sintering temperature is 600-1000°C, preferably 720-900°C, the primary sintering time is 4-48h, preferably 8-24h, and further preferably 12-20h.

[0026] In the above technical solution, pre-sintering is carried out before the primary sintering, and the pre-sintering is programmed temperature sintering. The heating rate is preferably 0.5-10°C / min, the pre-sintering temperature is 300-600°C, preferably 450-550°C, and further preferably 450-530°C. The pre-sintering time is 1-10h, preferably 4-8h.

[0027] In the above technical solution, the molar ratio of the intermediate product to the oxide of the Group IIIA element is 1:t, and the value range of t is greater than 0 to 0.05. Preferably, the molar ratio of the intermediate product to the oxide of the Group IIIA element is 1:(0.005-0.05).

[0028] In the above technical solution, the secondary sintering is programmed temperature sintering, the heating rate is preferably 0.5-10°C / min, the secondary sintering temperature is 100-700°C, preferably 150-600°C, further preferably 380-600°C, and the secondary sintering time is 0.5-10h, preferably 1-8h.

[0029] The third aspect of the present invention provides the use of the above-mentioned positive electrode material in a lithium battery.

[0030] Compared with the prior art, the present invention has the following beneficial effects:

[0031] 1. The cathode material of the present invention is a secondary microsphere formed by primary particles arranged radially along the secondary microsphere, wherein the primary particles are long strips with an aspect ratio of 1.05-60.0, and the surface is coated with oxides of group IIIA elements as a modification aid. The cathode material of the present invention has excellent electrochemical performance and good safety performance, and has the advantages of high discharge specific capacity, high first-cycle coulomb efficiency and high thermal runaway trigger temperature. The cathode material provided by the present invention can be used in high energy density and high safety lithium batteries.

[0032] 2. In the preparation process of the positive electrode material of the present invention, the positive electrode material precursor with a flaky morphology, the lithium source, and the modifier of the Group VA element are first mixed, and after a primary sintering, the intermediate product obtained is mixed with the oxide of the Group IIIA element and subjected to a secondary sintering. During the sintering process, the crystallization process of the primary particles of the positive electrode material is adjusted by the synergistic effect of the flaky morphology of the precursor, the modifier containing the Group VA element and the oxide of the Group IIIA element, as well as the control of the sintering temperature and sintering time. The morphology of the primary particles of the positive electrode material obtained is long strips, and is arranged along the radial direction of the secondary microspheres of the positive electrode material. The material with this composition and structure is more conducive to the diffusion of lithium ions, and can improve the first-week coulomb efficiency and discharge specific capacity of the material. At the same time, the material structure of this composition and structure is more stable, which can inhibit the formation and growth of microcracks in the material and has better safety. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 is a SEM image of the positive electrode material prepared in Example 1 of the present invention;

[0034] Figure 2 is a SEM image of a cross section of the positive electrode material prepared in Example 1 of the present invention;

[0035] Figure 3 0.1C rate charge and discharge curve of the positive electrode material prepared in Example 1 of the present invention;

[0036] Figure 4 This is the thermal safety test result of a full battery assembled with the positive electrode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0037] The technical solution of the present invention is described in detail below.

[0038] The first aspect of the present invention provides a lithium battery positive electrode material, the lithium ion battery positive electrode material comprises a chemical composition of Li a Ni x Co y M z N p O 2Compounds and modification aids, where M is selected from at least one element of Group VIIB or Group IIIA, N is selected from at least one element of Group VA, and the modification aids are selected from oxides containing Group IIIA elements. The cathode material Li a Ni x Co y M z N p O 2 Component N and the modification aid containing the oxide of Group IIIA element have a synergistic effect in improving the discharge capacity, first-cycle efficiency, and thermal runaway temperature of the material.

[0039] The lithium battery cathode material provided by the present invention has a chemical composition of Li a Ni x Co y M z N p O 2 compound, 0.9 ≤ a ≤ 1.2, 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, 0 ≤ z ≤ 1, 0 < p ≤ 0.1, preferably 0.5 ≤ x ≤ 0.95, 0 ≤ y ≤ 0.5, 0 ≤ z ≤ 0.5, 0 < p ≤ 0.05. When x, y, and z take values, they are not all 0 at the same time. Preferably, the values of x, y, and z are not 0, and the values of a, x, y, z, and p satisfy the principle of electroneutrality.

[0040] In an embodiment of the present invention, preferably, M is selected from Mn and / or Al. That is, preferably, the chemical composition of Li a Ni x Co y M z N p O 2 compound is Li a Ni x Co y MnzN p O 2 or Li a Ni x Co y Al z N p O 2 .

[0041] The lithium battery cathode material provided by the present invention, in terms of mole fractions:

[0042] Li a Ni x Co y M z N p O 2 compound 100 parts;

[0043] The amount of the modifying aid is greater than 0 parts and less than 5 parts, for example but not limited to 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, etc.

[0044] The lithium battery positive electrode material provided by the present invention, the oxide of the IIIA group element of the modification auxiliary agent has a chemical composition of Li a Ni x Co y M z N p O 2 A coating layer is formed on the surface of the compound.

[0045] The lithium battery positive electrode material provided by the present invention is a secondary microsphere formed by the accumulation of primary particles, wherein the primary particles are arranged along the radial direction of the secondary microsphere, and the median particle size of the secondary microsphere is 1-20 μm.

[0046] The lithium battery positive electrode material provided by the present invention has primary particles in the shape of elongated strips, and the aspect ratio of the primary particles is 1.05-60.0, preferably 1.5-30.0, and more preferably 1.5-20.0.

[0047] In the lithium battery positive electrode material provided by the present invention, the modification auxiliary agent, the Group IIIA element oxide, is selected from at least one of an oxide containing boron, an oxide containing aluminum, an oxide containing gallium, and an oxide containing indium. As a non-limiting example, it can be B 2 O 3 、Al 2 O 3 、Ga2O 3 、In2O 3 etc.

[0048] In a preferred embodiment of the present invention, the SEM image of the positive electrode material is as follows Figure 1 As shown. Figure 1 It can be seen that the cathode material of the present invention is a spherical secondary particle, the medium particle size of the spherical secondary particle is 10.1 μm, and the surface of the spherical particle contains a coating modification auxiliary agent. The SEM image of the cross section of the cathode material is as follows Figure 2 As shown. Figure 2 It can be seen that the primary particles are in the shape of long strips, and the primary particles are arranged along the radial direction of the secondary microspheres.

[0049] In the present invention, the scanning electron microscope image (SEM) is obtained by a scanning electron microscope of the ZEISS Merlin model produced by the German ZEISS company.

[0050] The inventors of the present invention conducted in-depth research on lithium battery positive electrode materials and creatively obtained lithium battery positive electrode materials with the above-mentioned composition and structural characteristics during the preparation of positive electrode materials. The positive electrode material with such characteristic composition and structure has higher discharge specific capacity and first-cycle coulombic efficiency, and has a higher thermal runaway trigger temperature when used in a full battery, and can be used in high-performance lithium batteries.

[0051] The second aspect of the present invention provides a method for preparing the above-mentioned positive electrode material, comprising:

[0052] (1) mixing a cathode material precursor, a lithium source, and a modifier containing a Group VA element, and sintering them once to obtain an intermediate product;

[0053] (2) The intermediate product is mixed with oxides of Group IIIA elements and subjected to secondary sintering to obtain the positive electrode material.

[0054] In the present invention, the chemical composition of the positive electrode material precursor is Ni x Co y M z (OH) 2 , 0≤x≤1, 0≤y≤1, 0≤z≤1, preferably 0.5≤x≤0.95, 0≤y≤0.5, 0≤z≤0.5, the values ​​of x, y and z are not 0 at the same time, and the values ​​of x, y and z satisfy the principle of electrical neutrality. As a non-limiting example, the typical chemical composition of the precursor can be Ni 0.5 Co 0.2 Mn 0.3 (OH) 2 、Ni 0.6 Co 0.2 Mn 0.2 (OH) 2 、Ni 0.8 Co 0.1 Mn 0.1 (OH) 2 、Ni 0.9 Co 0.05 Mn 0.05 (OH) 2 、Ni 0.95 Co 0.025 Mn 0.025 (OH) 2 、Ni 0.8 Co 0.15 Al 0.05 (OH) 2 The morphology of the positive electrode material precursor is microspheres formed by flake accumulation, and the thickness of the flakes is 1-500 nm, preferably 1-200 nm.

[0055] In the present invention, the lithium source may be in the form of a lithium salt, and the lithium salt is preferably selected from lithium nitrate (LiNO 3 )、LiCl、LiCO 2 CO 3 ), lithium hydroxide (LiOH), lithium hydroxide monohydrate (LiOH·H 2 O), lithium oxide (Li 2 O), lithium acetate (CH 3 COOLi and lithium oxalate (Li 2 C 2 O 4 ) at least one of.

[0056] In the present invention, the mixing of the cathode material precursor and the lithium source can be achieved by a high-speed mixer, a ball mill, a V-type mixer, a mechanical stirrer, a plowshare mixer, a double-helix cone mixer, or the like.

[0057] In the present invention, the molar ratio of the positive electrode material precursor to the lithium source (in terms of Li element) is 1:(0.9-1.2). As a non-limiting example, when the molar number of the precursor is 1, the molar number of the lithium source in terms of Li element can be 0.9, 0.95, 1.00, 1.05, 1.10, 1.15, 1.20, and any value in the range formed by any two of these values.

[0058] In the present invention, the modifier containing the Group VA element is preferably selected from at least one of nitrates, chlorides, carbonates, hydroxides, oxides, acetates and oxalates containing the Group VA element. As a non-limiting example, the modifier containing the Group VA element can be at least one of ammonium nitrate, ammonium chloride, antimony acetate, antimony oxide, bismuth oxalate, bismuth carbonate, phosphorus oxide, etc.

[0059] In the present invention, the molar ratio of the positive electrode material precursor and the modifier containing the VA group element (calculated as the VA group element) is 1:(0-0.1) and is not 0. As a non-limiting example, when the molar number of the precursor is 1, the molar number of the modifying aid calculated as the VA element can be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, and any value in the range formed by any two of these values. Preferably, the molar ratio of the precursor and the modifier containing the VA group element (calculated as the VA group element) is 1:(0.001-0.05).

[0060] In the present invention, the primary sintering is performed in an atmosphere furnace, and the sintering atmosphere may be at least one of air, oxygen, and an inert atmosphere such as nitrogen.

[0061] In the present invention, the primary sintering is programmed temperature sintering, and the temperature of the primary sintering is 600-1000°C, such as 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C and any range between any two values, more preferably, the temperature of the primary sintering is 720-900°C; the time of the primary sintering is 4-48h, such as 4h, 8h, 12h, 16h, 20h, 24h, 28h, 32h, 36h, 40h, 44h, 48h and any range between any two values, preferably, the time of the primary sintering is 8-24h, more preferably, the time of the primary sintering is 12-20h.

[0062] In the present invention, pre-sintering is carried out before the primary sintering, and the pre-sintering temperature is 300-600°C, such as 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C and any range between any two values. Preferably, the pre-sintering temperature is 450-550°C, more preferably, the pre-sintering temperature is 450-530°C; preferably, the pre-sintering time is 1-10h, such as 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h and any range between any two values. More preferably, the pre-sintering time is 4-8h.

[0063] In the present invention, there is no particular limitation on the heating rate of the primary sintering, and it is preferably 0.5-10°C / min, for example 0.5°C / min, 1°C / min, 2°C / min, 3°C / min, 5°C / min, 10°C / min, and any value in the range formed by any two of these values.

[0064] In the present invention, there is no special restriction on mixing the positive electrode material precursor, lithium source and modifier containing group VA element, and it can be achieved by high-speed mixer, ball mill, V-type mixer, mechanical stirring, plowshare mixer, double-helix cone mixer and the like.

[0065] In the present invention, the secondary sintering is performed in an atmosphere furnace, and the sintering atmosphere can be at least one of air, oxygen, and an inert atmosphere such as nitrogen.

[0066] In the present invention, the secondary sintering is programmed temperature sintering, and the temperature of the secondary sintering is 100-700°C, such as 100°C, 150°C, 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C and any range between any two values. Preferably, the temperature of the secondary sintering is 150-600°C, more preferably, the temperature of the secondary sintering is 380-600°C; the time of the secondary sintering is 0.5-10h, such as 0.5h, 1h, 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h and any range between any two values. More preferably, the time of the secondary sintering is 1-8h.

[0067] In the present invention, there is no particular limitation on the heating rate of the secondary sintering, and it is preferably 0.5-10°C / min, for example 0.5°C / min, 1°C / min, 2°C / min, 3°C / min, 5°C / min, 10°C / min, and any value in the range formed by any two of these values.

[0068] In the present invention, the molar ratio of the intermediate product to the oxide of the group IIIA element is 1:(0-0.05) and is not 0. As a non-limiting example, when the molar number of the intermediate product is 1, the molar number of the oxide of the group IIIA element can be 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.01, 0.015, 0.02, 0.0025, 0.03, 0.035, 0.04, 0.045, 0.05, and any value in the range formed by any two of these values. Preferably, the molar ratio of the intermediate product to the oxide of the group IIIA element is 1:(0.005-0.05).

[0069] The third aspect of the present invention provides a lithium battery positive electrode material prepared by the preparation method as described above.

[0070] Among them, the properties of the lithium battery positive electrode material have been described in detail in the first aspect and will not be repeated here.

[0071] The fourth aspect of the present invention provides the use of the positive electrode material as described above in a lithium battery. The lithium battery comprises: a positive electrode, comprising the positive electrode material as described above; a negative electrode; an electrolyte; and a separator. The positive electrode and the negative electrode can be prepared by coating and drying a composite for forming a positive electrode active material layer and a composite for forming a negative electrode active material layer on respective current collectors.

[0072] The positive electrode composite can be prepared by using a positive electrode active material, a conductive agent, a binder and a solvent.

[0073] The present invention has no specific restrictions on the conductive agent, as long as it has conductivity and remains stable within the charge and discharge range. The conductive agent can be at least one of acetylene black, ketjen black, artificial graphite, natural graphite, carbon tubes, graphene, superconducting carbon, carbon nanofibers, carbon dots, aluminum powder, nickel powder, titanium oxide, and conductive polymers.

[0074] The binder provides bonding between the positive electrode active material, the conductive agent and the current collector. The binder may be at least one of polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), water-based acrylic resin, polytetrafluoroethylene (PTFE), polyvinyl butyral (PVB), ethylene-vinyl acetate (EVA), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoroethylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylic resin.

[0075] The present invention has no specific restrictions on the current collector, as long as it has suitable conductivity. The current collector can be aluminum, nickel, copper, titanium, silver, stainless steel and carbon materials. The current collector can be processed into various forms such as foil, sheet, film, net, hole, non-woven fabric, etc.

[0076] The solvent may be N-methylpyrrolidone.

[0077] The negative electrode composite can be prepared by using a negative electrode active material, a conductive agent, a binder and a solvent.

[0078] The present invention has no special restrictions on the negative electrode active material, which can be selected according to actual needs. The negative electrode active material can be at least one of artificial graphite, natural graphite, soft carbon, hard carbon, mesophase microspheres (MCMB), carbon fiber, lithium metal, silicon, silicon oxide, lithium metal alloy, and lithium titanate.

[0079] The conductive agent and binder of the negative electrode of the present invention are not particularly limited, and can be the same type and content as those used in preparing the positive electrode. The current collector of the negative electrode can also be aluminum, nickel, copper, titanium, silver, stainless steel and carbon materials. The current collector can also be processed into various forms such as foil, sheet, film, mesh, hole, non-woven fabric, etc.

[0080] The electrolyte of the present invention is a liquid electrolyte, and the liquid electrolyte contains a lithium salt and a solvent, wherein the lithium salt and the solvent are not specifically limited.

[0081] The solvent may be a non-aqueous solvent, for example, at least one of ethylene carbonate (EC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), propylene carbonate (PC), ethyl propyl carbonate (EPC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), methyl formate (MF), ethyl formate (Eft), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), and propyl butyrate (BP).

[0082] The lithium salt may be LiPF 6 (Lithium hexafluorophosphate), LiBF 4 (lithium tetrafluoroborate), LiClO 4 (Lithium Perchlorate), LiAsF 6 (lithium hexafluoroarsenate), LiFSI (lithium bis(fluorosulfonyl imide), LiTFSI (lithium bis(trifluoromethanesulfonyl imide), LiTFS (lithium trifluoromethanesulfonate), LiDFOB (lithium difluorooxalatoborate), LiBOB (lithium bis(oxalatoborate), LiPO 2 F 2 At least one of Li(difluorophosphate), LiDFOP (lithium difluorooxalatephosphate), and LiTFOP (lithium tetrafluorooxalatoborate).

[0083] In order to improve the performance of lithium batteries, additives can be selectively added to the electrolyte, such as vinylene carbonate (VC), fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), tris(trimethylsilyl) phosphate (TMSP), sulfonate cyclic quaternary ammonium salt, ethylene sulfite (DTO), dimethyl sulfite (DMS), 1-propylene-1,3-sultone (PST), 4-propyl ethylene sulfate (PEGLST), diethyl sulfite (DES), adiponitrile (ADN), succinonitrile (SN), 1,3-propane sultone (1,3-PS), vinyl sulfate (DTD), 4-methylethylene sulfate (PCS), etc.

[0084] The separator is arranged between the positive and negative electrodes to isolate the positive and negative electrodes. The separator can be a polyolefin, such as polyethylene, polypropylene, a composite of polyethylene and polypropylene, or a sheet formed by glass fiber and a non-woven fabric. When a solid electrolyte is used, the solid electrolyte can also be used as a separator.

[0085] Next, the preparation method of the lithium battery is described, which is used to prepare the above-mentioned lithium battery. The main steps include: mixing the positive electrode material, conductive agent, binder and solvent evenly and coating them on at least one surface of the positive electrode current collector, drying, rolling and slicing them as the positive electrode; mixing the negative electrode material, conductive agent, binder and solvent evenly and coating them on at least one surface of the negative electrode current collector, drying, rolling and slicing them as the negative electrode; assembling the positive electrode plate, separator and negative electrode plate into a stacked or wound cell, placing the cell in a shell, injecting electrolyte and then packaging to obtain a lithium battery.

[0086] In the above-mentioned positive or negative electrode sheets, the amounts of the positive and negative electrode materials, conductive agents, and binders are not specifically limited. For example, based on the total amount of the positive or negative electrode materials, the mass content of the positive or negative electrode materials can be 50%-99%, the mass content of the conductive agent can be 0.5%-25%, and the mass content of the binder can be 0.5%-25%.

[0087] For year-on-year comparison, the mass ratio of positive electrode material: conductive agent: binder in the embodiment of the present invention is 90:5:5, acetylene black is used as the conductive agent, polyvinylidene fluoride (PVDF) is used as the binder, metallic lithium is used as the negative electrode in the button half-cell, graphite is used as the negative electrode material in the soft-pack full battery, the conductive agent is acetylene black, and the binder is sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR), wherein graphite: acetylene black: CMC: SBR = 95: 1.5: 2: 1.5, the diaphragm uses the American Celllgard 2400 polypropylene diaphragm, the electrolyte uses a liquid electrolyte, the solvent is a mixed solvent of ethylene carbonate (EC) and ethyl methyl carbonate (EMC), the volume ratio of the two is 3: 7, and the solute is lithium hexafluorophosphate LiPF 6 , the molar concentration is 1 mol / L.

[0088] The lithium battery in the embodiment of the present invention is assembled in an inert atmosphere glove box, and the moisture and oxygen content in the glove box is less than 0.1ppm. There is no special restriction on the battery model. For year-on-year comparison, the button battery model used in the embodiment of the present invention is 2025 type, the design capacity of the soft-pack full battery is 2Ah, and the electrochemical test conditions are: temperature is 25°C; voltage range is 2.8-4.3V. The thermal runaway trigger temperature of the soft-pack full battery is obtained by adiabatic accelerating calorimeter test, using heating-waiting-search mode, step temperature 10°C, waiting time 15min, search time 5min, maximum search temperature 250°C, and exothermic detection limit 0.03°C / min. The temperature corresponding to the heat release rate of the full battery reaching 1°C / min is the thermal runaway trigger temperature of the battery.

[0089] The present invention will be described in detail below through examples.

[0090] [Example 1]

[0091] This example is used to illustrate the preparation and evaluation method of the positive electrode material of the present invention.

[0092] (1) Preparation of positive electrode materials

[0093] Take the chemical composition of Ni 0.8 Co 0.1 Mn0 .1 (OH) 2 10 g of precursor (flaky, average thickness 30 nm) was added with lithium source LiOH·H 2 O and Bi 2 O 3 , so that the molar ratio of Li: precursor is 1.02:1, the molar ratio of Bi to precursor is 0.02:1, and the precursor, lithium source and Bi are mixed. 2 O 3 After mixing evenly, put it into a crucible for step-by-step sintering. The first step is to increase the temperature from room temperature to 450°C at 5°C / min and keep it warm for 6 hours. The second step is to increase the temperature from 450°C to 850°C at 5°C / min and keep it warm for 12 hours. Then, cool it naturally to obtain an intermediate product.

[0094] Gallium oxide was added to the intermediate product, the molar ratio of gallium oxide to the intermediate product was 3:100, the intermediate product and gallium oxide were mixed evenly and loaded into a crucible for sintering, the temperature was raised from room temperature to 400°C at 5°C / min, the temperature was kept for 6 hours, and then naturally cooled to obtain a positive electrode material.

[0095] (2) Evaluation of positive electrode materials

[0096] The SEM image of the positive electrode material is as follows Figure 1 As shown in the figure, it can be seen that the preparation method provided by the present invention can obtain a positive electrode material with good sphericity. The positive electrode material is a secondary microsphere formed by the accumulation of primary particles. The medium particle size of the secondary microsphere is 10.1 μm. The surface of the secondary microsphere obviously contains a coating material. Figure 1 The cross-sectional view of the positive electrode material shown in FIG. Figure 2 As shown, the primary particles of the positive electrode material are long strips, and the primary particles are arranged and distributed along the radial direction of the secondary microspheres, and the average aspect ratio of the primary particles is 12.8.

[0097] Take the above positive electrode material, acetylene black and 10% polyvinylidene fluoride solution, mix them evenly according to the mass ratio of positive electrode material: acetylene black: polyvinylidene fluoride 90:5:5, apply them on aluminum foil, dry the solvent, slice them to obtain positive electrode sheets, use lithium sheets as counter electrodes, and assemble the above positive electrode sheets into button lithium batteries in a glove box. The charge and discharge voltage range of button lithium batteries is 2.8-4.3V. The first discharge specific capacity at a rate of 0.1C is 211.1mAh / g, and the coulomb efficiency in the first week reaches 93.7%.

[0098] Taking graphite as the negative electrode material, the above-mentioned positive electrode sheets were assembled into a 2Ah soft-pack full battery for adiabatic accelerated calorimetry testing, and the thermal runaway trigger temperature reached 136.0°C.

[0099] [Example 2]

[0100] This example is used to illustrate the preparation and evaluation method of the positive electrode material of the present invention.

[0101] (1) Preparation of positive electrode materials

[0102] Take the chemical composition of Ni 0.8 Co 0.1 Mn0 .1 (OH) 2 10 g of precursor (flaky, average thickness 30 nm) was added with lithium source LiOH·H 2 O and Sb 2 O 3 , so that the molar ratio of Li: precursor is 1.1:1, the molar ratio of Sb to precursor is 0.05:1, and the precursor, lithium source and Sb 2 O 3 After mixing evenly, put it into a crucible for step-by-step sintering. The first step is to increase the temperature from room temperature to 500°C at 10°C / min and keep it warm for 6 hours. The second step is to increase the temperature from 500°C to 800°C at 10°C / min and keep it warm for 16 hours. Then, cool it naturally to obtain an intermediate product.

[0103] Indium oxide was added to the intermediate product, the molar ratio of indium oxide to the intermediate product was 4:100, the intermediate product and indium oxide were mixed evenly and loaded into a crucible for sintering, the temperature was raised from room temperature to 600°C at 10°C / min, the temperature was kept for 3 hours, and then naturally cooled to obtain a positive electrode material.

[0104] (2) Evaluation of positive electrode materials

[0105] SEM images of positive electrode materials and Figure 1 Similar to Figure 2The primary particles of the positive electrode material are long strips, and the primary particles are arranged and distributed along the radial direction of the secondary microspheres, and the average aspect ratio of the primary particles is 11.2. The median particle size of the secondary microspheres is 9.6 μm.

[0106] A lithium battery was prepared according to the method described in Example 1.

[0107] The charging and discharging voltage range of button lithium battery is 2.8-4.3V. The first discharge capacity at 0.1C rate is 209.5mAh / g, and the first week coulomb efficiency reaches 93.3%.

[0108] Graphite was used as the negative electrode material, and the above-mentioned positive electrode plates were assembled into a 2Ah soft-pack full battery for adiabatic accelerated calorimetry testing. The thermal runaway trigger temperature reached 132.5°C.

[0109] [Example 3]

[0110] (1) Preparation of positive electrode materials

[0111] Take the chemical composition of Ni 0.8 Co 0.1 Mn0 .1 (OH) 2 10 g of precursor (flaky, average thickness 30 nm) was added with lithium source LiOH·H 2 O and P 2 O 5 , so that the molar ratio of Li: precursor is 1.1:1, the molar ratio of P to precursor is 0.07:1, and the precursor, lithium source and P are mixed. 2 O 5 After mixing evenly, put it into a crucible for step-by-step sintering. The first step is to increase the temperature from room temperature to 550°C at 5°C / min and keep it warm for 4 hours. The second step is to increase the temperature from 550°C to 750°C at 10°C / min and keep it warm for 24 hours. Then, cool it naturally to obtain an intermediate product.

[0112] Alumina was added to the intermediate product with a molar ratio of alumina to the intermediate product being 1:100. The intermediate product and indium oxide were mixed evenly and then loaded into a crucible for sintering. The temperature was raised from room temperature to 650°C at a rate of 10°C / min, kept for 2 hours, and then naturally cooled to obtain a positive electrode material.

[0113] (2) Evaluation of positive electrode materials

[0114] SEM images of positive electrode materials and Figure 1 Similar to Figure 2 The primary particles of the positive electrode material are long strips, and the primary particles are arranged and distributed along the radial direction of the secondary microspheres, and the average aspect ratio of the primary particles is 8.6. The median particle size of the secondary microspheres is 10.3 μm.

[0115] A lithium battery was prepared according to the method described in Example 1.

[0116] The charging and discharging voltage range of button lithium battery is 2.8-4.3V. The first discharge capacity at 0.1C rate is 208.2mAh / g, and the first week coulomb efficiency reaches 92.7%.

[0117] Taking graphite as the negative electrode material, the above-mentioned positive electrode sheets were assembled into a 2Ah soft-pack full battery for adiabatic accelerated calorimetry testing, and the thermal runaway trigger temperature reached 129.7°C.

[0118] [Example 4]

[0119] (1) Preparation of positive electrode materials

[0120] Take the chemical composition of Ni 0.8 Co 0.15 Al 0.05 (OH) 2 10 g of precursor (flaky, average thickness 50 nm) was added with lithium source LiOH·H 2 O and P 2 O 5 , so that the molar ratio of Li: precursor is 1.1:1, the molar ratio of P to precursor is 0.1:1, and the precursor, lithium source and P are mixed. 2 O 5 After mixing evenly, put it into a crucible for step-by-step sintering. The first step is to increase the temperature from room temperature to 550°C at 5°C / min and keep it warm for 4 hours. The second step is to increase the temperature from 550°C to 750°C at 10°C / min and keep it warm for 9 hours. Then, cool it naturally to obtain an intermediate product.

[0121] Alumina was added to the intermediate product with a molar ratio of alumina to the intermediate product being 1:100. The intermediate product and indium oxide were mixed evenly and then loaded into a crucible for sintering. The temperature was raised from room temperature to 250°C at a rate of 10°C / min, kept for 2 hours, and then naturally cooled to obtain a positive electrode material.

[0122] (2) Evaluation of positive electrode materials

[0123] SEM images of positive electrode materials and Figure 1 Similar to Figure 2 The primary particles of the positive electrode material are long strips, and the primary particles are arranged and distributed along the radial direction of the secondary microspheres, and the average aspect ratio of the primary particles is 7.1. The median particle size of the secondary microspheres is 10.2 μm.

[0124] A lithium battery was prepared according to the method described in Example 1.

[0125] The charging and discharging voltage range of button lithium battery is 2.8-4.3V. The first discharge capacity at 0.1C rate is 202.5mAh / g, and the first week coulomb efficiency reaches 90.8%.

[0126] Graphite was used as the negative electrode material, and the above-mentioned positive electrode plates were assembled into a 2Ah soft-pack full battery for adiabatic accelerated calorimetry testing. The thermal runaway trigger temperature reached 120.3°C.

[0127] [Example 5]

[0128] (1) Preparation of positive electrode materials

[0129] Take the chemical composition of Ni 0.8 Co 0.1 Mn0 .1 (OH) 2 10 g of precursor (flaky, average thickness 30 nm) was added with lithium source LiOH·H 2 O and P 2 O 5 , so that the molar ratio of Li: precursor is 1.1:1, the molar ratio of P to precursor is 0.03:1, and the precursor, lithium source and P are mixed. 2 O 5 After mixing evenly, put it into a crucible for step-by-step sintering. The first step is to increase the temperature from room temperature to 500°C at 5°C / min and keep it warm for 4 hours. The second step is to increase the temperature from 500°C to 750°C at 10°C / min and keep it warm for 12 hours. Then, cool it naturally to obtain an intermediate product.

[0130] Alumina was added to the intermediate product in a molar ratio of 1:100. The intermediate product and indium oxide were mixed evenly and then loaded into a crucible for sintering. The temperature was raised from room temperature to 500°C at a rate of 10°C / min, kept for 2 hours, and then naturally cooled to obtain a positive electrode material.

[0131] (2) Evaluation of positive electrode materials

[0132] SEM images of positive electrode materials and Figure 1 Similar to Figure 2 The primary particles of the positive electrode material are long strips, and the primary particles are arranged and distributed along the radial direction of the secondary microspheres, and the average aspect ratio of the primary particles is 10.5. The median particle size of the secondary microspheres is 9.7 μm.

[0133] A lithium battery was prepared according to the method described in Example 1.

[0134] The charging and discharging voltage range of button lithium battery is 2.8-4.3V. The first discharge capacity at 0.1C rate is 210.8mAh / g, and the first week coulomb efficiency reaches 92.9%.

[0135] Taking graphite as the negative electrode material, the above-mentioned positive electrode sheets were assembled into a 2Ah soft-pack full battery for adiabatic accelerated calorimetry testing, and the thermal runaway trigger temperature reached 131.9°C.

[0136] [Comparative Example 1]

[0137] (1) Preparation of positive electrode materials

[0138] Take the chemical composition of Ni 0.8 Co 0.1 Mn0 .1 (OH) 2 10 g of precursor (flaky, average thickness 30 nm) was added with lithium source LiOH·H 2 O, so that the molar ratio of Li: precursor is 1.02:1. The precursor and lithium source are mixed evenly and then loaded into a crucible for step-by-step sintering. The first step is to heat from room temperature to 450°C at 5°C / min and keep warm for 6h. The second step is to heat from 450°C to 850°C at 5°C / min and keep warm for 12h. Then, the cathode material is naturally cooled to obtain the cathode material.

[0139] (2) Evaluation of positive electrode materials

[0140] SEM images of positive electrode materials and Figure 1 The cross-sectional image obtained after focused ion beam cutting shows that the primary particles of the positive electrode material are short and thick particles. The primary particles have no specific arrangement and are in a disordered stacking state. The average aspect ratio of the primary particles is 1.22. The median particle size of the secondary microspheres is 9.8μm.

[0141] A lithium battery was prepared according to the method described in Example 1.

[0142] The charging and discharging voltage range of button lithium battery is 2.8-4.3V. The first discharge capacity at 0.1C rate is 195.3mAh / g, and the first week coulomb efficiency reaches 87.1%.

[0143] Taking graphite as the negative electrode material, the above-mentioned positive electrode plates were assembled into a 2Ah soft-pack full battery for adiabatic accelerated calorimetry testing, and the thermal runaway trigger temperature reached 108.7°C.

[0144] [Comparative Example 2]

[0145] (1) Preparation of positive electrode materials

[0146] Take the chemical composition of Ni 0.8 Co 0.1 Mn0 .1 (OH) 2 10 g of precursor (flaky, average thickness 30 nm) was added with lithium source LiOH·H 2 O and Bi 2 O3 , so that the molar ratio of Li: precursor is 1.02:1, the molar ratio of Bi to precursor is 0.02:1, and the precursor, lithium source and Bi are mixed. 2 O 3 After mixing evenly, put it into a crucible for step-by-step sintering. The first step is to increase the temperature from room temperature to 450°C at 5°C / min and keep it warm for 6 hours. The second step is to increase the temperature from 450°C to 850°C at 5°C / min and keep it warm for 12 hours. Then cool it naturally to obtain the positive electrode material.

[0147] (2) Evaluation of positive electrode materials

[0148] SEM image of cathode material precursor Figure 1 The cross-sectional view obtained after cutting the positive electrode material with a focused ion beam shows that the primary particles of the positive electrode material are long strips, and the primary particles are arranged and distributed along the radial direction of the secondary microspheres, and the average aspect ratio of the primary particles is 5.28. The median particle size of the secondary microspheres is 10.2μm.

[0149] A lithium battery was prepared according to the method described in Example 1.

[0150] The charging and discharging voltage range of button lithium battery is 2.8-4.3V. The first discharge capacity at 0.1C rate is 201.7mAh / g, and the first week coulomb efficiency reaches 90.9%.

[0151] Taking graphite as the negative electrode material, the above-mentioned positive electrode plates were assembled into a 2Ah soft-pack full battery for adiabatic accelerated calorimetry testing, and the thermal runaway trigger temperature reached 115.9°C.

[0152] [Comparative Example 3]

[0153] (1) Preparation of positive electrode materials

[0154] Take the chemical composition of Ni 0.8 Co 0.1 Mn0 .1 (OH) 2 10 g of precursor (flaky, average thickness 30 nm) was added with lithium source LiOH·H 2 O, so that the molar ratio of Li: precursor is 1.02:1. The precursor and the lithium source are mixed evenly and then loaded into a crucible for step-by-step sintering. The first step is to increase the temperature from room temperature to 450°C at 5°C / min and keep it warm for 6h. The second step is to increase the temperature from 450°C to 850°C at 5°C / min and keep it warm for 12h. Then, it is naturally cooled to obtain an intermediate product.

[0155] Gallium oxide was added to the intermediate product, the molar ratio of gallium oxide to the intermediate product was 3:100, the intermediate product and gallium oxide were mixed evenly and loaded into a crucible for sintering, the temperature was raised from room temperature to 400°C at 5°C / min, the temperature was kept for 6 hours, and then naturally cooled to obtain a positive electrode material.

[0156] (2) Evaluation of positive electrode materials

[0157] SEM image of cathode material precursor Figure 1 The cross-sectional image obtained after focused ion beam cutting shows that the primary particles of the positive electrode material are short and thick particles. The primary particles have no specific arrangement and are in a disordered stacking state. The average aspect ratio of the primary particles is 1.31. The median particle size of the secondary microspheres is 10.1μm.

[0158] A lithium battery was prepared according to the method described in Example 1.

[0159] The charging and discharging voltage range of button lithium battery is 2.8-4.3V. The first discharge capacity at 0.1C rate is 192.1mAh / g, and the first week coulomb efficiency reaches 86.6%.

[0160] Taking graphite as the negative electrode material, the above-mentioned positive electrode plates were assembled into a 2Ah soft-pack full battery for adiabatic accelerated calorimetry testing, and the thermal runaway trigger temperature reached 111.6°C.

[0161] [Comparative Example 4]

[0162] (1) Preparation of positive electrode materials

[0163] Compared with Example 1, the difference is that the precursor morphology is that the primary particles are microspheres formed by spindle agglomeration.

[0164] (2) Evaluation of positive electrode materials

[0165] SEM images of positive electrode materials and Figure 1 Similarly, the cross-sectional image obtained after focused ion beam cutting shows that the primary particles of the positive electrode material are short and thick particles, and the primary particles have no specific arrangement and are in a disordered stacking state. The average aspect ratio of the primary particles is 1.42. The median particle size of the secondary microspheres is 9.8μm.

[0166] A lithium battery was prepared according to the method described in Example 1.

[0167] The charging and discharging voltage range of button lithium battery is 2.8-4.3V. The first discharge capacity at 0.1C rate is 194.8mAh / g, and the first week coulomb efficiency reaches 87.5%.

[0168] Taking graphite as the negative electrode material, the above-mentioned positive electrode sheets were assembled into a 2Ah soft-pack full battery for adiabatic accelerated calorimetry testing, and the thermal runaway trigger temperature reached 112.1°C.

[0169] The above describes the specific implementation of the present invention in detail, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the various technical features being combined in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A cathode material, comprising a compound with a chemical composition of Li a Ni x Co y M z N p O2 and a modification aid. In the compound with a chemical composition of Li a Ni x Co y M z N p O2, 0.9 ≤ a ≤ 1.2, 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, 0 ≤ z ≤ 1, 0 < p ≤ 0.

1. The values of x, y, and z are not all 0 at the same time, and the values of a, x, y, z, and p satisfy the principle of electroneutrality. The M is selected from at least one of the elements in Group VIIB or Group IIIA, the N is selected from at least one of the elements in Group VA, and the modification aid is selected from the oxides containing the elements in Group IIIA; the cathode material is a secondary microsphere formed by the aggregation of primary particles, and the primary particles are strip-shaped.

2. The positive electrode material according to claim 1, characterized in that The chemical composition is Li a Ni x Co y M z N p In the compound of O2, 0.5 ≤ x ≤ 0.95, 0 ≤ y ≤ 0.5, 0 ≤ z ≤ 0.5, 0 < p ≤ 0.

05. The values of x, y, and z are not all 0 at the same time. Preferably, the values of x, y, and z are all non-zero, and the values of a, x, y, z, and p satisfy the principle of electroneutrality.

3. The positive electrode material according to claim 1, characterized in that In mole fractions: Li a Ni x Co y M z N p 100 parts of compound of O2; The amount of the modifying aid is greater than 0 parts and less than 5 parts.

4. The positive electrode material according to claim 1, characterized in that The oxide of the IIIA group element of the modification aid has a chemical composition of Li a Ni x Co y M z N p A coating layer is formed on the surface of the O2 compound.

5. The positive electrode material according to claim 1, characterized in that The primary particles are arranged along the radial direction of the secondary microspheres, and the median particle size of the secondary microspheres is 1.0-20.0 μm.

6. The positive electrode material according to claim 5, characterized in that The aspect ratio of the primary particles is 1.05-60.0, preferably 1.5-30.0, and more preferably 1.5-20.

0.

7. A method for preparing the positive electrode material according to any one of claims 1 to 6, comprising: (1) mixing a cathode material precursor, a lithium source, and a modifier containing a Group VA element, and sintering them once to obtain an intermediate product; (2) The intermediate product is mixed with oxides of Group IIIA elements and subjected to secondary sintering to obtain the positive electrode material.

8. The preparation method according to claim 7, characterized in that: The chemical composition of the precursor is Ni x Co y M z (OH)2, 0≤x≤1, 0≤y≤1, 0≤z≤1, preferably 0.5≤x≤0.95, 0≤y≤0.5, 0≤z≤0.5, the values ​​of x, y and z are not 0 at the same time, and the values ​​of x, y and z satisfy the principle of electrical neutrality.

9. The preparation method according to claim 7, characterized in that: The lithium source is selected from at least one of lithium nitrate, lithium chloride, lithium carbonate, lithium hydroxide, lithium hydroxide monohydrate, lithium oxide, lithium acetate and lithium oxalate; And / or, the modifier containing a Group VA element is selected from at least one of nitrates, chlorides, carbonates, hydroxides, oxides, acetates and oxalates containing a Group VA element.

10. The preparation method according to claim 7, characterized in that: The molar ratio of the cathode material precursor and the lithium source is 1:(0.9-1.2) based on the Li element; And / or, the molar ratio of the positive electrode material precursor and the modifier containing the Group VA element is 1:s, calculated as the Group VA element, and the value of s ranges from greater than 0 to 0.1, preferably 1:(0.001-0.05); And / or, the molar ratio of the intermediate product to the oxide of the Group IIIA element is 1:t, and the value of t ranges from greater than 0 to 0.05, preferably 1:(0.005-0.05).

11. The preparation method according to claim 7, characterized in that: The primary sintering temperature is 600-1000°C, preferably 720-900°C, and the primary sintering time is 4-48h, preferably 8-24h, and more preferably 12-20h; And / or, the temperature of the secondary sintering is 100-700° C., preferably 150-600° C., more preferably 380-600° C., and the time of the secondary sintering is 0.5-10 h, preferably 1-8 h.

12. The preparation method according to claim 7, characterized in that: The morphology of the positive electrode material precursor is microspheres formed by flake accumulation; the average thickness of the flakes is 1-500nm, preferably 1-200nm.

13. Use of the positive electrode material according to any one of claims 1 to 6 in a lithium battery.